2006
DOI: 10.4161/cbt.5.2.2313
|View full text |Cite
|
Sign up to set email alerts
|

ENU administration causes genomic instability along with single nucleotide polymorphisms in p53 during gliomagenesis: T11TS administration demonstrated in vivo apoptosis of these genetically altered tumor cells

Abstract: Advancement of molecular analysis of neoplastic cells demonstrated that multiple genetic changes are associated with the development of tumors. Cancer cell must exhibit a mutator phenotype, which is likely to be responsible for the genomic instability found in cancer tissues. The mutator phenotype, such as defective mismatch repair, is known to cause microsatellite instability, which is associated with certain cases of sporadic cancer. Previously many studies have been carried out to determine the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Previous studies have reported that ENU affected the expression of genes such as p21-Ras (Engelbergs et al 2000) and p53 (Katayama et al 2005a;Mukherjee et al 2006), closely related to the modulation of morphogenic and The graph shows concentrations of VEGF 165 obtained by ELISA assay for samples with normal blood content (blue box) and for samples of exsanguinated animals after perfusion with saline (green box). The differences between conditions was of p<0.05 and among groups (control, CO classic oligodendroglioma and AO anaplastic oligodendroglioma) of p<0.001.…”
Section: Vegf Expressionmentioning
confidence: 99%
“…Previous studies have reported that ENU affected the expression of genes such as p21-Ras (Engelbergs et al 2000) and p53 (Katayama et al 2005a;Mukherjee et al 2006), closely related to the modulation of morphogenic and The graph shows concentrations of VEGF 165 obtained by ELISA assay for samples with normal blood content (blue box) and for samples of exsanguinated animals after perfusion with saline (green box). The differences between conditions was of p<0.05 and among groups (control, CO classic oligodendroglioma and AO anaplastic oligodendroglioma) of p<0.001.…”
Section: Vegf Expressionmentioning
confidence: 99%
“…The patients with malignant gliomas remain poorly responsive to multimodality therapeutic interventions, including surgery, radiotherapy, and chemotherapy [11, 12]. It has been reported that tumor growth is dependent on not only the rate of cellular proliferation, but also that of cell death [13].…”
Section: Discussionmentioning
confidence: 99%
“…Further study in our lab also deciphered that T11TS immunotherapy, mediate functional activation of T cells by rectifying gliomagenic anti-proliferative action on T-cell by correcting CD2-mediated nuclear factor of activated T-cell calcineurin pathway [38] . Some of our previous publications also delineated that T11TS reduces glioma mass simultaneously by accelerating the apoptotic death of brain tumor cells and by decreasing the number of dividing glioma-bearing cells [39,40] .…”
Section: Introductionmentioning
confidence: 92%